Topological hall signatures of two chiral spin textures hosted in a single tetragonal inverse heusler thin film - Sivakumar, Pranava K.; Goebel, Boerge; Lesne, Edouard; Markou, Anastasios; Gidugu, Jyotsna; Taylor, James M.; Deniz, Hakan; Jena, Jagannath; Felser, Claudia; Mertig, Ingrid; Parkin, Stuart S. P. (ACS nano, 2020)
Magnetic skyrmions and antiskyrmions are observed in material classes with different crystal symmetries, where the Dzyaloshinskii-Moriya interaction stabilizes either skyrmions or antiskyrmions. Here, we report the observation of two distinct peaks in the topological Hall effect in a thin film of Mn2RhSn. Utilizing a phenomenological approach and electronic transport simulations, these topological Hall effect features are attributed to be direct signatures of two topologically distinct chiral spin objects, namely, skyrmions and antiskyrmions. Topological Hall effect studies allow us to determine the existence of these two topological objects over a wide range of temperature and magnetic fields. In particular, we find skyrmions to be stable at low temperatures, suggesting the increased importance of dipolar interactions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Antiskyrmions; Inverse Heusler thin films; Noncollinear spin textures; Skyrmions; Topological Hall effect